Frequency detection using Pade approximation - Barkhudaryan, Artur; Mkrtchyan, Sergey (Armenian Journal of Mathematics, 2008)
The current paper describes an application of Pade approximation to obtain a frequency detection method similar to (and, in a sense, more general than) linear prediction. While generally not applicable for spectrum estimation, the described method is in many cases more precise in finding the frequencies of a harmonic signal. A great number of numerical tests were performed for comparing frequency detection performance of the method under consideration and of linear prediction. Their methodology and results are summarized in the article.